Dampak Konversi Hutan Menjadi Perkebunan Kelapa Sawit Terhadap Keanekaragaman dan Kelimpahan Kupu-kupu Superfamili Papilionoidea - Daawia Daawia; Nurlita Dianingsih (Jurusan Biologi FMIPA Universitas Cenderawasih, 2023)
The research was conducted in June to August 2022 in Ubiyau Village, Yanamaa Village and Yuwanain Village, Arso District, Keerom, Papua. The aim of the study was to determine the impact of forest conversion to oil palm plantations on the diversity and abundance of the Superfamily Papilionoidea butterfly. The line transect count method was used for sampling butterflies with a transect length of 1500 m at each study area. Sampling was carried out along a line transect in an imaginary box measuring 10 x 10 x 10 m which was carried out on sunny days from 09.00 am to 14.00 pm. The highest species diversity of the Superfamily Papilionoidea was found in Secondary Forest (HS), namely 70 species consisting of Papilionidae (8 species), Pieridae (5 species), Lycaenidae (21 species) and Nymphalidae (36 species). There were 42 species of butterflies recorded from Non-Productive Oil palm Plantations consisting of Papilionidae (5 species), Pieridae (4 species), Lycaenidae (11 species) and Nymphalidae (22 species). While the lowest number of butterfly species was encountered in Productive Oil Palm Plantations namely 32 species consisting of Papilionidae (5 species), Pieridae (3 species), Lycaenidae (8 species) and Nymphalidae (16 species). These data indicated that conversion of secondary forest to oil palm plantations reduced butterfly species by around 40-53%. The highest Shannon-Wiener Diversity Index (H') and Margalef Diversity Index (Dmg) values were found in secondary forest (H'=3.4; Dmg =13.7) followed by Non-Productive Oil Palm Plantations (H'=2.5; Dmg=7.2) and Productive Oil Palm Plantations (H=2.0; Dmg=6.1). The highest species similarity was between Secondary Forest and Productive Oil Palm Plantations with Sorensen Index value IS=60%, followed by Non-Productive Oil Palm Plantations and Productive Oil Palm Plantations (IS=51%) and the lowest species similarity index was between Secondary Forests and Non-Productive Oil Palm Plantations (IS = 46%). In Secondary Forest the composition of the number of individuals per species tends to be more evenly distributed compared to oil palm plantations. Forest conversion to Oil Palm Plantations has a negative impact on butterfly species diversity of the Superfamily Papilionoidea. The lost species that were not found in oil palm plantations were forest specialist species with small range sizes and niches as well as specific diets that were only found in forest. Key words: Papilionidae; primary forest; Pieridae; Nymphalidae; Lycaenidae; Keerom.